2011
DOI: 10.1166/jnn.2011.3900
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Characteristics of Ge-Based Metal-Insulator-Semiconductor Devices with Ge<SUB>3</SUB>N<SUB>4</SUB> Dielectrics Formed by Plasma Nitridation

Abstract: We have fabricated pure germanium nitrides (Ge3N4) using high-density plasma nitridation and investigated electrical properties of Au/Ge3N4/Ge capacitors. We achieved equivalent oxide thickness (EOT) of 1.4 nm, and dielectric constant of Ge3N4 was estimated to be 9.7. The gate leakage current density of 4.3 A/cm2 in the accumulation condition at V(fb)-1 V, where V(fb) is the flatband voltage, was one order of magnitude lower than that of conventional poly-Si/SiO2/Si stacks. The interface state density (D(it)) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…Ge 3 N 4 has been known since 1930, when the hexagonal phenacite structure (ground-state b phase, space group: P6 3 /m) was first synthesized by exposing the germanium powder to the ammonia atmosphere at 973 K [4,5]. Ruddlesden and Popper [6] have found that the a phase (space group: P3 1 /c) is closely related to b-Ge 3 N 4 , but is generally believed to be a metastable phase under ambient conditions [7,8]. g-Ge 3 N 4 has been synthesized from the Ge powders under high temperature-pressure conditions [9] or by shock-wave compression [10].…”
Section: Introductionmentioning
confidence: 99%
“…Ge 3 N 4 has been known since 1930, when the hexagonal phenacite structure (ground-state b phase, space group: P6 3 /m) was first synthesized by exposing the germanium powder to the ammonia atmosphere at 973 K [4,5]. Ruddlesden and Popper [6] have found that the a phase (space group: P3 1 /c) is closely related to b-Ge 3 N 4 , but is generally believed to be a metastable phase under ambient conditions [7,8]. g-Ge 3 N 4 has been synthesized from the Ge powders under high temperature-pressure conditions [9] or by shock-wave compression [10].…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] Moreover, pure germanium nitrides (Ge 3 N 4 ) formed by plasma nitridation have exhibited superior physical properties over GeO 2 , such as higher thermal stability. [14][15][16][17] Although the electrical property of Ge 3 N 4 /Ge metal-insulator-semiconductor (MIS) capacitors can be found in the literature, 18,19) physical characteristics of Ge 3 N 4 /Ge structures need to be further understood for process optimization. Several reports have estimated the chemical shift in Ge 3d core-level photoelectron spectra measured for Ge 3 N 4 surfaces to be about +2.3 eV through conventional X-ray photoelectron spectroscopy (XPS), but without strictly considering the spin-orbit splitting.…”
Section: Introductionmentioning
confidence: 99%
“…These values are in excellent agreement with earlier experimentally reported values for Ge 3 N 4 . 38 No imaginary phonon frequencies were found for any of the considered configurations. The static dielectric constants ( 0 ) presented in this study include the vibrational contribution and hence are in better agreement with the experimental results than previously reported first principles results.…”
Section: A Sigen Materialsmentioning
confidence: 89%